(untitled) (Bangladesh Journal of Zoology, 2016)
The intestinal parasites and their prevalence and intensity of infestation was investigated. A total of 793 stool samples were examined from the out patients of Dhaka medical College Hospital. Eggs and lavae of six species of intestinal parasites were recovered, of which two species were protozoans: Entamoeba histolytica Schaudinn, 1903; and Giardia intestinalis (Lambl, 1859) and four species of helminthes: Ascaris lumbricoides Linnaeus, 1758; Trichuris trichiura (Linnaeus, 1771) Stiles, 1901; Ancylostoma duodenale (Dubini, 1843) Creplin, 1845; and Enterobius vermicularis (Linnaeus, 1758)]. The overall prevalence of infestation was 43.253% and egg per gram (EPG) of infestation was slightly higher in males than females. Prevalence of intestinal helminth was found higher than intestinal protozoans. Among the six species of intestinal parasites, Ascaris lumbricoides showed highest prevalence (21.689%) and Enterobius vermicularis lowest prevalence (1.008%). Among the patients of the hospital, highest prevalence (83.333%) was observed in 0 - 10 years age group and lowest (30.167%) in 51 - 60 years age-group. Bangladesh J. Zool. 44(1): 89-97, 2016